An exploratory study of expectant mothers’ knowledge, attitudes and beliefs about infant vaccination - Bradshaw, Amanda; Carter, Carolyn G. (Qualitative Health Communication, 2022)
Background: Childhood vaccination decision making occurs during pregnancy. However, more insight is needed to determine how expectant mothers in the United States decide whether to vaccinate their children — particularly as the first vaccine, Hepatitis B, is recommended within 24 hours of birth. Aim: This qualitative study used the foundational lens of the Theory of Reasoned Action to 1) explore how expectant mothers formulate knowledge, attitudes, and beliefs about infant vaccination, and 2) discern if differences exist regarding how first-time expectant mothers approach vaccine decision making. Methods: Eleven focus groups were conducted with pregnant participants from an obstetrics practice in the southeastern United States. Thematic analysis was undertaken, utilizing the constant comparative method. Results: Four overarching themes emerged: the need for evidence-based childhood vaccine information during pregnancy; perceptions of source trustworthiness and the social media paradox; concerns about the “one-size-fits-all” vaccine schedule; and the process of vaccine risk-benefit analysis of first-time mothers. Discussion: Practical implications highlight a need for standardized vaccine-related education during the prenatal care period. Theoretical implications reveal that the decision of whether to vaccinate one’s infant remains complex, involving a variety of factors. Conclusion: Compared to expectant mothers who had children previously, first-time expectant mothers especially reported feeling ill-informed to make infant vaccine decisions.